Deep Anterior Lamellar Keratoplasty followed by Toric Lens Implantation for the Treatment of Concomitant Anterior Stromal Diseases and Cataract. Issue 1 (2017) - Scorcia, Vincenzo; Lucisano, Andrea; Savoca Corona, Vincenzo; De Luca, Valentina; Carnevali, Adriano; Busin, Massimo
Purpose: To evaluate the outcomes of deep anterior lamellar keratoplasty (DALK) followed by phacoemulsification and toric intraocular lens (IOL) implantation for the treatment of concomitant stromal disease and cataract. Methods: In this retrospective non-comparative interventional case series, ten eyes affected by stromal disease and cataract underwent DALK followed by phacoemulsification with toric IOL implantation after a minimum period of 5 months from complete suture removal. In each case, topographic astigmatism, refraction, visual acuity, and endothelial cell density were recorded before DALK and 1, 6, and 12 months after cataract surgery. In addition, IOL rotation was evaluated using anterior segment optical coherence tomography. Results: Big-bubble DALK was performed in all eyes but one that received manual dissection. Topographic astigmatism averaged 5.6 ± 2.2 diopters (D) after suture removal; refractive astigmatism decreased to 0.55 ± 0.61 D as early as one month after cataract surgery and did not change substantially throughout the follow-up period. In all patients, one month after phacoemulsification uncorrected and best spectacle-corrected visual acuity were, respectively, ≥20/40 and ≥20/25 with a residual spherical equivalent of 0.00 ± 0.84 D. At the latest follow-up visit, in all cases the IOL rotation was ≤5 degrees from the intended position and the endothelial cell loss within 8.5%. No complications were recorded. Conclusions: DALK followed by phacoemulsification with toric IOL implantation optimizes visual and refractive outcomes in patients with concomitant stromal disease and cataract. In comparison with a combined procedure, the sequential approach offers better predictability of the postoperative refraction in the absence of an increased risk of complications.